The Influence of School Culture on the Academic Achievement of Students - Riska Ayu Lestari; Irawan Hadi Patanggu; Masmur M. (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to examine the influence of school culture on students’ academic achievement in madrasahs. According to various sources, students’ academic achievement in Indonesia remains relatively low, as evidenced by various national and international educational assessment results. One factor suspected of influencing academic achievement is school culture. Therefore, this study aims to analyze the influence of school culture on the academic achievement of students at State Madrasah Tsanawiyah 3 in Palu City. This study employs a quantitative approach. The research sample consists of 40 students selected through purposive sampling. Data collection for this study involved distributing a Likert-scale questionnaire on the school culture variable and using report card grades as an indicator of students’ academic achievement for the academic performance variable of ninth-grade students. Validity was tested using item-total correlation, and reliability was assessed using Cronbach’s Alpha. Data analysis was conducted using SPSS version 26 via simple linear regression. The results indicate that school culture has a positive but insignificant influence of 5.7% on students’ academic achievement. These findings suggest that school culture has a positive but insignificant influence on student achievement in madrasahs.